Functional characterization of GNE mutations prevalent in Asian subjects with GNE myopathy, an ultra-rare neuromuscular disorder - Sharma, Shweta; Chanana, Pratibha; Bharadwaj, Ravi; Bhattacharya, Sudha; Arya, Ranjana (Biochimie, 2022)
UDP-GlcNAc 2-epimerase/ManNAc kinase (GNE) is a bifunctional enzyme (N-terminal epimerase and C-terminal Kinase domain) that catalyses the rate limiting step in sialic acid biosynthesis. More than 200 homozygous missense or compound heterozygous mutations in GNE have been reported worldwide to cause a rare neuromuscular disorder, GNE myopathy. It is characterized by a slowly progressive defect in proximal and distal skeletal muscles with patients becoming wheel-chair-bound. There are no current approved therapies available for GNE myopathy. ManNAc therapy is currently in advanced clinical trials and has shown signs of slowing the disease progression in a phase 2 trial. The present study aims to understand the effect of GNE mutation on its enzymatic activity and identification of potential small effector molecules. We characterized different GNE mutations (p.Asp207Val, p.Val603Leu, p.Val727Met, p.Ile618Thr and p.Arg193Cys) prevalent in Asian population that were cloned, expressed and purified from Escherichia coli as full-length recombinant proteins. Our study demonstrates that full length GNE can be expressed in E. coli in its active form and analysed for the functional activity. Each mutation showed variation in epimerase and kinase activity and responded to the small effector molecules (metformin, BGP-15 kaempferol, catechin, quercetin) in a differential manner. Our study opens an area for futuristic structural determination of full length GNE and identification of potential therapeutic molecules. [Display omitted] •Recombinant GNE was purified from E. coli in functionally active form.•A drug screening mechanism was described for testing small effector molecules.•The anti-diabetic drug metformin improved functional activity of mutated GNE.